(untitled) (Journal of Dhaka National Medical College & Hospital, 2014)
This observational cross-sectional study was conducted to understand factors for compliance of epilepsy patients. This study was done in epilepsy clinic of Department Neurology, Dhaka Medical College &Hospital, from February to June 2010. A total of 100 patients were included in the study. Epileptic patients who had been prescribed medication for more than three months were included for this study. Data collected on variables of interest were analyzed using different approaches including Chi-squared (2) statistical analysis.56% of the patients has found non-compliant at some or multiple stages of prescribed medication. 55% of noncompliant is due to monetary reason. Location, Family size and monthly income of patient’s family were socioeconomic factors that had statistical significance when it comes to compliance (p < 0.05). Gender and age did not have statistical significance. It was also observed that counseling was a statistically significant factor when it observed amongst study population. Similarly patient who sought alternative treatment was found to be more non compliant. It was observed that patients on phenobarbital was found to be mostly (88%) compliant and patients on sodium valproate or phenytoin were least compliant (20%). J. Dhaka National Med. Coll. Hos. 2014; 20 (02): 30-32